Memahami Tafsir Al-Qur`an Dengan Kaidah Bahasa Arab - Irsyad Al Fikri Ys; Asep Fu’ad; Iwan Caca Gunawan (LPPAIK Universitas Muhammadiyah Bandung, 2021)
The Qur'an was revealed using Arabic which is very beautiful, the friends and Arabs who know and feel the uslub-uslub Arabic understand very well what was revealed to the Prophet. But most of the people who are not from the Arab nation are very difficult to communicate in Arabic, especially to understand the Qur'an. Departing from these problems, understanding the rules of the Arabic language is very closely related to the verses of the Qur'an. Without the rules of Arabic, it is very difficult to understand the Qur'an. So the purpose of writing this article is to explain the rules of the Arabic language as an analytical tool in order to understand the contents of the Qur'an. The method used in this research is descriptive analytic with the type of library research. The results of this study indicate that, someone who will interpret the Qur'an is required to understand the rules of the Arabic language, even the scholars make the rules of the Arabic language as conditions that must be met for a commentator to understand the content of the verses of the Qur'an. - The Qur'an correctly in accordance with existing rules. Among these rules include nahwu science, neuroscience and balaghah science